Risk of potential hepatotoxicity from pirfenidone or nintedanib in patients with idiopathic pulmonary fibrosis: results of a retrospective analysis of a large insurance database in Taiwan - Liao, Kuang-Ming; Chen, Chung-Yu (Frontiers in Pharmacology, 2024)
A growing population of individuals diagnosed with idiopathic pulmonary fibrosis (IPF) are receiving treatment with nintedanib and pirfenidone. The aim of our study was to assess the incidence of drug-induced liver injury (DILI) associated with the use of pirfenidone and nintedanib in patients with IPF in Taiwan.We collected a cohort of adult patients diagnosed with IPF between 2017 and 2020. The research outcomes involved assessing the incidence of DILI in patients treated with nintedanib or pirfenidone.Poisson regression analysis was employed to estimate incidence rates, with and without adjustments for covariates, to calculate and present both unadjusted and adjusted incidence rate ratios (IRRs).The risk of DILI was greater in patients who received nintedanib than in those who received pirfenidone during the one-year follow-up. Patients treated with nintedanib exhibited a heightened risk of DILI based on inpatient diagnoses using specific codes after adjusting for variables such as gender, age group, comorbidities and concomitant medications, with an adjusted incidence rate ratio (aIRR) of 3.62 (95% confidence interval (CI) 1.11-11.78). Similarly, the risk of DILI was elevated in patients treated with nintedanib according to a per-protocol Poisson regression analysis of outcomes identified from inpatient diagnoses using specific codes. This was observed after adjusting for variables including gender, age group, comorbidities, and concomitant medications, with an aIRR of 3.60 (95% CI 1.11-11.72).Data from postmarketing surveillance in Taiwan indicate that patients who received nintedanib have a greater risk of DILI than do those who received pirfenidone.